2011
DOI: 10.3171/2010.4.jns10118
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of traumatic brain injury with thymosin β4 in rats

Abstract: Object This study was designed to investigate the efficacy of delayed thymosin β4 (TB4) treatment of traumatic brain injury (TBI) in rats. Methods Young adult male Wistar rats were divided into the following groups: 1) Sham group (6 rats); 2) TBI + Saline group (9 rats); 3) and TBI + Tβ4 group (10 rats). TBI was induced by controlled cortical impact over the left parietal cortex. Thymosin β4 (6 mg/kg) or saline was administered intraperitoneally starting at Day 1 and then every 3 days for an additional 4 dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 70 publications
8
77
0
1
Order By: Relevance
“…We previously demonstrated a strong association of T␤4 treatment with OL differentiation in in vivo and in in vitro models (5)(6)(7)23). The results of this study further support our central hypothesis of T␤4-mediated oligodendrogenesis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We previously demonstrated a strong association of T␤4 treatment with OL differentiation in in vivo and in in vitro models (5)(6)(7)23). The results of this study further support our central hypothesis of T␤4-mediated oligodendrogenesis.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, T␤4 promotes cardiomyocyte and keratinocyte migration in these models. T␤4 improves functional outcome after experimental induction of multiple sclerosis, embolic stroke, and traumatic brain injury (5)(6)(7). In all three models, improvement in neurological outcome is associated with oligodendrogenesis (i.e.…”
Section: Thymosin ␤4 (T␤4)mentioning
confidence: 99%
“…Several recent studies have reported that treatments that protect or restore neurogenesis following TBI are associated with improved spatial learning [72][73][74][75]. Furthermore, Zhang et al [76] found that inhibition of neurogenesis with intraventricular cytosine arabinoside reversed the restorative effects of erythropoietin on post-TBI Morris Water maze performance.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that thymosin β4 is capable of promoting new blood vessel formation via stimulating the differentiation and directional migration of endothelial cells (17,18). These activities of thymosin β4 play an important role in dermal and corneal wound healing and in recovery from acute myocardial infarction and traumatic brain injury (11,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have suggested that thymosin β4 is capable of promoting new blood vessel formation via stimulating the differentiation and directional migration of endothelial cells (17,18). These activities of thymosin β4 play an important role in dermal and corneal wound healing and in recovery from acute myocardial infarction and traumatic brain injury (11,(19)(20)(21).However, whether thymosin β4 is effective in alleviating inflammatory response and pancreatic tissue injury in SAP has not yet been elucidated. The present study investigated the effect of thymosin β4 on pancreatic injury following SAP, to identify whether it could be a good candidate for attenuating the severity of SAP.…”
mentioning
confidence: 99%